2018
DOI: 10.1002/2017wr021521
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Snow Water Equivalent Estimated From GPS Vertical Displacements: A Synthetic Loading Case Study for Western U.S. Mountains

Abstract: GPS monitoring of solid Earth deformation due to surface loading is an independent approach for estimating seasonal changes in terrestrial water storage (TWS). In western United States (WUSA) mountain ranges, snow water equivalent (SWE) is the dominant component of TWS and an essential water resource. While several studies have estimated SWE from GPS‐measured vertical displacements, the error associated with this method remains poorly constrained. We examine the accuracy of SWE estimated from synthetic displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…The RMSE for this epoch was 40.07 kg/m 2 , which agrees with previous results for Yunnan Province, China, published by Zhang et al [18], of about 48-52 kg/m 2 at annual time scales based on monthly values, which are smoother than daily solutions used in the present study. Likewise, RMSEs in the range of 25-77 kg/m 2 across the mountains of the western United States were reported by Enzminger et al [16], after using synthetic data to assess the inversion of radial displacements into TWS. Moreover, on the basis of the results of the checkerboard test and the closed-loop simulation, it was found that generally, the results were relatively good near the GPS sites (Figures 6c and 7c).…”
Section: Rms Of Twsmentioning
confidence: 62%
See 2 more Smart Citations
“…The RMSE for this epoch was 40.07 kg/m 2 , which agrees with previous results for Yunnan Province, China, published by Zhang et al [18], of about 48-52 kg/m 2 at annual time scales based on monthly values, which are smoother than daily solutions used in the present study. Likewise, RMSEs in the range of 25-77 kg/m 2 across the mountains of the western United States were reported by Enzminger et al [16], after using synthetic data to assess the inversion of radial displacements into TWS. Moreover, on the basis of the results of the checkerboard test and the closed-loop simulation, it was found that generally, the results were relatively good near the GPS sites (Figures 6c and 7c).…”
Section: Rms Of Twsmentioning
confidence: 62%
“…Furthermore, GPS-imaged TWS could be used to fill in the temporal gap between the GRACE and GRACE-FO missions, as well as validate their estimations. However, this might be possible only for regions with a dense GPS network [16], although reasonable results have been reported for a relatively small number of stations [18]. Here, 397 GPS stations were considered from which only (at most) 353 were available, with an average of 314 stations having daily solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We corrected for smoothing-related mass leakage from the SN to its surroundings (Enzminger et al, 2018). Monthly empirical gain factors were derived from a synthetic ΔS time series using data from PRISM 10.1029/2019GL084589…”
Section: Seasonal δS From Gps Dzmentioning
confidence: 99%
“…Li et al, 2016), soil moisture (Girotto et al, 2019;Tian et al, 2019), evapotranspiration (X. Li, Long, et al, 2019;Long, Longuevergne, & Scanlon et al, 2014), and snow and glaciers (Castellazzi et al, 2019;Chen et al, 2017;Enzminger et al, 2018), by assimilating GRACE observations (Brookfield et al, 2018;Han et al, 2019;Houborg et al, 2012;Kumar et al, 2016;. However, they cannot provide complete information brought by the GRACE satellites; some aquifers and/or human water use are often overlooked, such as deep groundwater storage (GWS) and cropland irrigation (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%